SWOT Analysis Of Bunga Tutoring Course Institutions In Banjar Baru City: Exploring Potential And Challenges - Milatina, Siti Wirdiyana (Nurul Jadid University, 2024)
In an increasingly connected era of globalization, expertise in foreign languages, especially Arabic, is becoming an important asset for individuals across different backgrounds. This article analyzes the course institution Bimbel Bunga in Banjar Baru City, which offers Arabic language learning programs. Using a SWOT analysis approach, this research explores the strengths, weaknesses, opportunities, and threats facing the institution. The strengths of Tutoring Bunga lie in the flexibility of learning time and the number of competent tutors. However, weaknesses in the provision of teaching materials and less focus on language fluency are challenges that need to be overcome. Opportunities to become a leading course institution are increasingly open with the increasing public interest in learning Arabic, while threats from fierce competition and dwindling teaching tutors require proactive strategies to ensure program sustainability. This research method uses a descriptive qualitative approach, with data collection through interviews and observations. The results showed that Bimbel Bunga has great potential to grow by implementing innovations in teaching, improving teaching materials, and using technology. With the right strategy, this institution can improve the quality of Arabic language education and meet the growing needs of the community.